Microscopic vision modeling method by direct mapping analysis for micro-gripping system with stereo light microscope. (April 2016) - Wang, Yuezong; Zhao, Zhizhong; Wang, Junshuai
Highlights: A microscopic vision modeling method is proposed which consists of four parts. This method is applied in micro-gripping system with stereo light microscope. Image distortion and disparity distortion correction methods are proposed. Initial model outputs initial reconstruction data. Residual compensation model outputs high-precision reconstruction data. Abstract: We present a novel and high-precision microscopic vision modeling method, which can be used for 3D data reconstruction in micro-gripping system with stereo light microscope. This method consists of four parts: image distortion correction, disparity distortion correction, initial vision model and residual compensation model. First, the method of image distortion correction is proposed. Image data required by image distortion correction comes from stereo images of calibration sample. The geometric features of image distortions can be predicted though the shape deformation of lines constructed by grid points in stereo images. Linear and polynomial fitting methods are applied to correct image distortions. Second, shape deformation features of disparity distribution are discussed. The method of disparity distortion correction is proposed. Polynomial fitting method is applied to correct disparity distortion. Third, a microscopic vision model is derived, which consists of two models, i.e., initial vision model and residual compensation model. We derive initial vision model by the analysis of direct mapping relationship between object and image points. Residual compensation model is derived based on the residual analysis of initial vision model. The results show that with maximum reconstruction distance of 4.1 mm in X direction, 2.9 mm in Y direction and 2.25 mm in Z direction, our model achieves a precision of 0.01 mm in X and Y directions and 0.015 mm in Z direction. Comparison of our model with traditional pinhole camera model shows that two kinds of models have a similar reconstruction precision of X coordinates. However, traditional pinhole camera model has a lower precision of Y and Z coordinates than our model. The method proposed in this paper is very helpful for the micro-gripping system based on SLM microscopic vision.